2017
DOI: 10.1016/j.drugalcdep.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Victimization as a mediator of alcohol use disparities between sexual minority subgroups and sexual majority youth using the 2015 National Youth Risk Behavior Survey

Abstract: Background Alcohol use among underage youth is a significant public health concern. According to the National Institute on Alcohol Abuse and Alcoholism, alcohol is the “drug of choice” among adolescents, meaning more youth use and abuse alcohol than any other substance. Prevalence of alcohol use is disproportionately higher among sexual minority youth (SMY) than among their heterosexual peers. We examined sexual identity and sexual behavior disparities in alcohol use, and the mediational role of bullying in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…Researchers found higher rates of verbal aggression among female same-sex couples than different-sex couples; however, verbal aggression was not associated with HED or cannabis use [61]. Adolescent SMW were more likely than their age-matched heterosexual counterparts to report cyber and school-based peer bullying [37, 24], experiences that were associated with alcohol and drug use [25, 84, 57, 58, 24]. Bullying was a particularly strong predictor of risky alcohol use among bisexual youth, a finding that was not consistently found for other SGMY sub-groups [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found higher rates of verbal aggression among female same-sex couples than different-sex couples; however, verbal aggression was not associated with HED or cannabis use [61]. Adolescent SMW were more likely than their age-matched heterosexual counterparts to report cyber and school-based peer bullying [37, 24], experiences that were associated with alcohol and drug use [25, 84, 57, 58, 24]. Bullying was a particularly strong predictor of risky alcohol use among bisexual youth, a finding that was not consistently found for other SGMY sub-groups [37].…”
Section: Resultsmentioning
confidence: 99%
“…Adolescent SMW were more likely than their age-matched heterosexual counterparts to report cyber and school-based peer bullying [37, 24], experiences that were associated with alcohol and drug use [25, 84, 57, 58, 24]. Bullying was a particularly strong predictor of risky alcohol use among bisexual youth, a finding that was not consistently found for other SGMY sub-groups [37]. Across a number of studies, felt stigma was also associated with substance use, but adolescent SMW reported significantly higher levels of felt stigma than adolescent SMM [64].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings showed a predominance of psychological/ verbal violence and the use of licit drugs, especially alcohol and tobacco. Studies in this field conducted in Brazil, United States, Italy, and Australia support these same findings in the LGBT population (Pellulo et al, 2013;McCabe et al, 2010;de Santis et al, 2014;Teixeira-Filho & Rondini, 2012;Vieira, 2006;Laranjeira, 2014;Thiede et al, 2003;Phillips et al, 2017). The greater ease of access and purchase and low supervision justifies this finding.…”
Section: Discussionmentioning
confidence: 75%
“…It could be, for example, that girls are more susceptible to substance use as the result of peer victimization and thus more likely to use at higher rates. 43,44 Studies of adults support this supposition. 45 The increase in risk among youth who are unsure of their sexual identity also deserves attention.…”
Section: Figurementioning
confidence: 98%